Real and structural convergence in the Romanian counties in the pre-accession and post-accession periods - Mihaela-Nona Chilian; Marioara Iordan; Carmen Beatrice Pauna (European Regional Science Association (ERSA), 2016)
In the European Union, one of the primary goals of integration is the convergence of the regional income per capita (and of other significant socio-economic indicators), and hence, how to generate a process of convergence. In the economic literature, theories of convergence and divergence examine the reasons for diminishing or increasing the disparities between the rich and the poor re¬gions, and in the case of divergence, explain the persistence of such disparities. In particular, the real convergence approaches are connected to the study of long-term economic growth, economic development and the dynamics of complex economic sectors with high economic and social impacts, and also to the supporting/unsporting institutions and economic mechanisms (market structure, distribution of economic results). Concomitantly, the structural convergence has deserved less attention; although it is an important process for both building and functioning of the single economic and monetary area and for the development of the Member States and their regions. Studies have found that there is a correlation between structural convergence and income (real) convergence, though the findings differ in what regards the strength and direction of such a connection. Starting from the concepts of real and structural convergence, the paper presents an analysis of the real and structural convergence processes in the Romanian counties during the pre-accession and post-accession periods, based on specific indicators (GDP per capita, gross speed of convergence, variation coefficient, gross labor productivity, gross productivity growth rate). Also, with the help of real convergence indices and structural coefficients, the presence and evolution of the relationship between real and structural convergence at sub-regional level is revealed. The results show that the analyzed convergence processes had different speeds in Romania, and that counties have adapted differently to the new economic environment of the EU single market, conditional on their pre-accession development level. The counties which during the pre-accession period recorded good performances have usually strengthened their positions after the EU accession, while the counties with lower performances generally revealed slower growth and convergence, despite recording faster growth rates over certain short periods. Especially regarding productivity convergence, the situation is worrisome for the poorest counties of Romania, but also for some of the counties with higher development level. The real convergence was generally aligned with the structural convergence in the Romanian counties, but again only the most developed counties recorded post-accession progresses in both the convergence processes. Such results are in line with the findings of other studies on the economic and structural convergence of the Member States and/or their regions, but also reveal the sub-regional peculiarities of the catching up and development processes going on in the Romanian economy, and call for more effective implementation of the national and EU development policies at all levels.
Keywords: O47; R11; R12; 330; real convergence; convergence indicators; structural convergence; structural coefficients; Romanian regions and counties